Kesiapan Guru Kelas Melaksanakan Layanan Bimbingan dan Konseling di Sekolah Dasar Se-Kota Padang - Suci Mustika Putri; Khairani Khairani; Yusri Yusri (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
Readiness is someone condition that makes it ready to give a response in makes the point particular to the situation. This research intent for (1) describe teacher readiness braze to perform guidance and counselling service at elementary school one City of Padang is seen of science aspect, (2) describe teacher readiness braze to perform guidance and counselling service at elementary school the one City of Padang is seen of skill aspect, (3) describe teacher readiness braze to perform guidance and counselling service at elementary school the one City of Padang is seen of attitude aspect. This observational type is observational descriptive quantitative. Indigenous observational population teacher brazes elementary school (SD) one City of total Padang 429 teachers braze 4, 5 and 6. The sample were taken to utilize Technic Cluster Random Sampling, so gotten by sample amount as much 37 teachers braze 4, 5, and 6. Research performed by administers instrument questionnaires. Data analysed by percentage analysis. The research findings reveal the teacher readiness braze to perform guidance and counselling service at elementary school one City of Padang in the good category.